Transcriptome Analysis of Dimethyl Fumarate Inhibiting the Growth of Aspergillus carbonarius - Siruo Wang; Bowen Tai; Xifan Yu; Erfeng Li; Gang Wang; Jing Jin; Fuguo Xing (Toxins, 2025)
Aspergillus carbonarius is one of the main pathogens responsible for postharvest diseases in fruits and is also one of the main ochratoxin A-producing strains. It not only causes significant economic losses but also poses a risk to human health. We found an inhibitory effect of dimethyl fumarate fumigation on the growth of A. carbonarius. To further explore its antifungal mechanism, this study elucidated the functions of key pathway-related genes through a transcriptomics analysis. A total of 1402 differentially expressed genes (DEGs) were identified, including 987 up-regulated and 415 down-regulated genes. Dimethyl fumarate was found to significantly inhibit the growth of A. carbonarius by disrupting cell integrity and obstructing mycelium growth and secondary metabolism. These findings provide a basis for the potential application of dimethyl fumarate in the food industry to inhibit A. carbonarius and subsequent ochratoxin A contamination.